ESTIMASI STOK KARBON MANGROVE DI KAWASAN PERIZINAN BERUSAHA PEMANFAATAN HUTAN UNIVERSITAS LAMBUNG MANGKURAT - Erwin Rif'at Nazari; Syarifuddin Kadir; Abdul Hadi; Badaruddin Hamdie (Universitas Lambung Mangkurat, 2026)
Mangrove ecosystems in the PBPH area of Lambung Mangkurat University, Kotabaru Regency, store substantial blue carbon that is important for climate-mitigation strategies and local sustainable management. This study estimated vegetation carbon stocks and described soil organic carbon characteristics in Block II (Tanjung Tengah and Tanjung Sungkai) using purposive plots guided by Sentinel-2 NDVI classification into sparse, moderate, and dense canopy classes. Nine 10 × 10 m plots were established, tree DBH and height were measured for allometric biomass estimation, and soil samples were collected at 0–30 cm and 30–60 cm to determine %C-organic and bulk density. The study area covered approximately 79.18 ha with a total vegetation carbon stock of about 2203.77 t C, while mean vegetation carbon density reached around 162.08 t C/ha; dense stands dominated total carbon contribution due to their large areal extent. Soil measurements showed relatively high organic carbon across plots, with %C-organic ranging from 7.34 to 17.45 and bulk density ranging from 0.51 to 1.11 g/cm³. These findings strengthen site-level blue-carbon data and indicate that maintaining the integrity of dense mangrove areas and improving degraded stands can jointly secure vegetation and soil carbon benefits in the PBPH ULM landscape.